2006
DOI: 10.4171/jems/60
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness and stability of ground states for some nonlinear Schrödinger equations

Abstract: We discuss the orbital stability of standing waves of a class of nonlinear Schrödinger equations in one space dimension. The crucial feature for our treatment is the presence of a nonconstant linear potential that is even and decreasing away from the origin in space. This enables us to establish the orbital stability of all ground states over the whole range of frequencies for which such solutions exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, 0 = inf σ(L 2 λ ) by the positivity of ϕ λ , as before. It is proved in Lemma 3.4 of ( [30]) that, for all λ < Λ, 0 / ∈ σ(L 1 λ ) and L 1 λ has exactly one negative eigenvalue.…”
Section: Global Branch In the Self-focusing Casementioning
confidence: 99%
“…Furthermore, 0 = inf σ(L 2 λ ) by the positivity of ϕ λ , as before. It is proved in Lemma 3.4 of ( [30]) that, for all λ < Λ, 0 / ∈ σ(L 1 λ ) and L 1 λ has exactly one negative eigenvalue.…”
Section: Global Branch In the Self-focusing Casementioning
confidence: 99%
“…Note that (E2)-(E4) can be satisfied by a function g of the type (7.14). Theorem 7.1 gives a complete description of all positive solutions of (7.12) and, as is shown in Stuart (2006), these solutions have a variational characterization as 'ground states'. For the homogeneous case (7.14), it is easy to show that solutions of (7.12) cannot change sign.…”
Section: Example 2 the Functionmentioning
confidence: 99%
“…In Stuart (2006), it is shown that the conditions introduced in Grillakis et al (1987) to justify the V-K criterion are also satisfied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors considered the stability of the standing wave solutions to a Schrödinger equation (see [4,11,12,15,21]); some authors studied the existence of ground states or bounded states of a Schrödinger equation (see [1,3,5,8,14,25]); and others are interested in the stability of standing wave solutions to a Schrödinger equation with potential (see [9,26,29] and the references therein). In this paper, we will deal with not only the existence of ground states but also the stability of standing wave solutions to (1.1).…”
Section: Introductionmentioning
confidence: 99%